3D quantitative comparative analysis of long bone diaphysis variations in microanatomy and cross‐sectional geometry - Houssaye, Alexandra (J Anat, 2018)
Long bone inner structure and cross‐sectional geometry display a strong functional signal, leading to convergences, and are widely analyzed in comparative anatomy at small and large taxonomic scales. Long bone microanatomical studies have essentially been conducted on transverse sections but also on a few longitudinal ones. Recent studies highlighted the interest in analyzing variations of the inner structure along the diaphysis using a qualitative as well as a quantitative approach. With the development of microtomography, it has become possible to study three‐dimensional (3D) bone microanatomy and, in more detail, the form–function relationships of these features. This study focused on the selection of quantitative parameters to describe in detail the cross‐sectional shape changes and distribution of the osseous tissue along the diaphysis. Two‐dimensional (2D) virtual transverse sections were also performed in the two usual reference planes and results were compared with those obtained based on the whole diaphysis analysis. The sample consisted in 14 humeri and 14 femora of various mammalian taxa that are essentially terrestrial. Comparative quantitative analyses between different datasets made it possible to highlight the parameters that are strongly impacted by size and phylogeny and the redundant ones, and thus to estimate their relevance for use in form‐function analyses. The analysis illustrated that results based on 2D transverse sections are similar for both sectional planes; thus if a strong bias exists when mixing sections from the two reference planes in the same analysis, it would not problematic to use either one plane or the other in comparative studies. However, this may no longer hold for taxa showing a much stronger variation in bone microstructure along the diaphysis. Finally, the analysis demonstrated the significant contribution of the parameters describing variations along the diaphysis, and thus the interest in performing 3D analyses; this should be even more fruitful for heterogeneous diaphyses. In addition, covariation analyses showed that there is a strong interest in removing the size effect to access the differences in the microstructure of the humerus and femur. This methodological study provides a reference for future quantitative analyses on long bone inner structure and should make it possible, through a detailed knowledge of each descriptive parameter, to better interpret results from the multivariate analyses associated with these studies. This will have direct implications for studies in vertebrate anatomy, but also in paleontology and anthropology.